Comparative analysis of the chemical composition and size of starch granules in grain between diploid and tetraploid sweetcorn cultivars - E. B. Khatefov; V. I. Khoreva; Yu. A. Kerv; T. V. Shelenga; V. V. Sidorova; Y. N. Demurin; V. G. Goldstein (Труды по прикладной ботанике, генетике и селекции)
Background. Improving the taste and nutritional value of sweetcorn using genetic selection techniques is an important trend. The tetraploid sugary maize cultivar ‘Baksanskaya sakharnaya’ (k-23426) has a number of advantages in terms of taste and marketability over traditional diploid varieties.The purpose of the research was to identify the distinctive biochemical characteristics that affect the taste of this cultivar in comparison with the diploid reference (cv. ‘Rannyaya Lakomka’, с-1775).Materials and methods. The differences in phenotypic traits between diploid (2n) and tetraploid (4n) maize plants were assessed. Infrared spectroscopy was used to study the difference in the biochemical composition of kernels in terms of protein, starch and oil content. Accumulation of metabolites in a dry kernel was studied using gas–liquid chromatography with mass spectrometry.Results. Comparison of the phenotypic traits in 2n and 4n sweetcorn plants showed that 4n had a better ear structure, protein and oil content. Analysis of metabolites showed that quantitative indicators of chemical components changed in kernels of the 4n sweetcorn without changing the qualitative composition. The chemical composition of the metabolites in 4n sweetcorn grain was characterized by an increase in the synthesis of most organic acids and protein amino acids, phosphoric acid, fatty acids, some monosaccharides, phenolic compounds, and phytosterols. A decrease in the content of most polyhydric alcohols, disaccharides, trisaccharides, some monosaccharides, and phenolic compounds was observed. An inhibitory effect of a su2 gene dose on the size of starch granules was found. Conclusion. The studies showed the advantage of the 4n sweetcorn over the 2n one due to its improved ear structure and biochemical composition, which positively affected the taste qualities.